(3eTGQa GdCfhGQ Ydi UMGM GdCKGQs - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eXgQ hdjfg GdeHjf , hMGFWI ef THg GdeHWdjf , hJMQja GdLGgdjf HYKg eMeOkG Udi Gddg Ydjg hSde Edi cGaI NdbI HcJGHg GdPj dG jCJjI GdHGWd ef Hjf jOjg s
(3BNQgG (B:s
(3hVe CUGHYg ceG bGd ai GdMOjK GdBNQ cgGJjf hbQf CKGHYI hGddg SHMGfg hJYGdi CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
Keywords: (3eJaQbGJs